2000
DOI: 10.1034/j.1399-0039.2000.550501.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Pacific/Asian populations inferred from HLA class II allele frequency distributions

Abstract: The allele frequency distributions for the HLA class II loci, DRB1, DQB1 and DPB1, in eight Pacific/Asian populations: Hawaiian, Samoan, Malay, Papua New Guinea (PNG) Highlands, and two Indonesian and PNG Lowland groups, were determined using high-resolution polymerase chain reaction/sequence-specific oligonucleotide probe (PCR/SSOP) typing methods. The allele frequency distributions for the HLA-DRB1 locus were determined for a third Indonesian population as well as for an additional Filipino population. DRB1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
75
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(90 citation statements)
references
References 31 publications
15
75
0
Order By: Relevance
“…These studies found similar allele distribution patterns for most populations and loci. As with Native American populations (described above), the degree of differentiation was higher among populations from southeast Asia, Polynesia, Melanesia and Australia [35][36][37][38][39][40] than the rest of the world, and populations from these areas display reduced diversity in allelic lineages. The distribution of HLA alleles in 'island type' populations also resembled the ones described above for Native Americans; in the populations from Oceania, the DRB1 locus has more allelic lineages and appears to present higher degrees of differentiation.…”
Section: Hla Studies In Other Populationsmentioning
confidence: 75%
“…These studies found similar allele distribution patterns for most populations and loci. As with Native American populations (described above), the degree of differentiation was higher among populations from southeast Asia, Polynesia, Melanesia and Australia [35][36][37][38][39][40] than the rest of the world, and populations from these areas display reduced diversity in allelic lineages. The distribution of HLA alleles in 'island type' populations also resembled the ones described above for Native Americans; in the populations from Oceania, the DRB1 locus has more allelic lineages and appears to present higher degrees of differentiation.…”
Section: Hla Studies In Other Populationsmentioning
confidence: 75%
“…Again, the differences can be explained by the small number of populations being averaged and the correspondingly large influence of outliers (such as the Javanese and Indonesian populations) in the Salamon et al study. Mack et al [4] concluded that the high F nd values observed in these OCE outlier populations were the result of selection in response to a local pathogen. Valdes et al [226] examined variation of class II loci, considered at the locus and amino acid level, in 22 populations from the 12th IHW, with similar results to those of the Salamon et al study.…”
Section: Locus-level Comparisons With Previous Studiesmentioning
confidence: 99%
“…Population-level studies of HLA allelic diversity have provided insight into the selective forces that have acted to generate and maintain polymorphism in the human species [2,3]. Historical and evolutionary relationships among modern human populations have been inferred from comparisons of HLA allele and haplotype frequency distributions [4][5][6][7]. Further, variation in the allelic diversity between populations, as well as comparisons of linkage disequilibrium (LD) patterns across the HLA region, have been used to infer demographic events such as bottlenecks and founder events [3,8].…”
Section: Introductionmentioning
confidence: 99%
“…Watterson (1978) proposed that deviation from such an equilibrium is an indicator of departures from neutrality and hence selection. The so-called Ewens-Watterson test of neutrality has been used to confirm the effects of balancing selection acting on the MHC in both non-model species (Paterson, 1998;Miller et al, 2001;Hambuch and Lacey, 2002) and humans (Mack et al, 2000;Begovich et al, 2001).…”
Section: Detecting Selection In Contemporary Populationsmentioning
confidence: 99%